Analysis of the structure and content of the merdeka curriculum on green chemistry materials - Real Fandi; Faizah Qurrata Aini; Zonalia Fitriza (Jurnal Pijar Mipa, 2023)
This research aims to describe the compatibility between the structure and content of Merdeka’s curriculum on green chemistry based on the revised Bloom's Taxonomy, Dave and Dyers' Taxonomy, and chemistry textbooks. This research is descriptive with a qualitative approach with a content structure analysis research design derived from the Model of Educational Reconstruction (MER). The data collection technique was carried out based on a literature study, while the data analysis technique was carried out based on the Milles and Huberman data analysis technique. The instruments used were standard content analysis tables and structural analysis tables. The standard content analysis table was prepared according to the revised Bloom's and Dave and Dyers' taxonomy. The content structure analysis table measures the breadth of the material, guided by the senior high school textbook from the Ministry of Education and Culture, and the depth of the material is guided by the Handbook of Green Chemistry and Technology by James Clark & Duncan Macquarrie. The research results obtained  (1) Elements of chemical understanding were following the revised Bloom taxonomy, (2) Elements of process skills only dominated abstract skills, (3) Elements of the Pancasila student profile contained abstract skills and the realm of attitude. Whereas in content analysis, (1) the breadth of material on the learning outcomes of green chemistry is by high school books from the Ministry of Education and Culture, (2) the depth of material contained in high school chemistry textbooks published by the Ministry of Education and Culture has not explained in more detail less in presenting the questions, and some material is was not suitable to be placed for phase E high school based on the Merdeka’s curriculum.